2018
DOI: 10.1007/s40544-018-0219-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the tribo-chemical smoothening process between self-mated silicon carbide in a water-lubricated surface-contact reciprocating test

Abstract: Silicon carbide (SiC) can be tribo-chemically smoothened during a self-mated sliding procedure in the aqueous environment. As well reported in the point-contact tests, this smoothening process works well due to the abundant water as oxidant. After this smoothening process, the tribo-surface is well polished, a closely mated tribo-gap naturally forms, and an ultra-low friction state is built. However, water in the tribo-gap could be insufficient in industrial applications, e.g., the seal gap in mechanical seals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In Figure a, it can be found that water plays a decisive role in lubrication of the PDA tribofilm. Interestingly, Si 3 N 4 would also react with water, resulting in a colloidal silica layer as a good lubricant, as shown in reactions and . , However, water in the Si 3 N 4 /metal interface could be insufficient under boundary lubrication, which is difficult to form a stable colloidal silica layer . Meanwhile, in PDA-aq, the PDA tribofilm is hydrophilic and can strongly form a stable “solid-like” water film on the interface .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In Figure a, it can be found that water plays a decisive role in lubrication of the PDA tribofilm. Interestingly, Si 3 N 4 would also react with water, resulting in a colloidal silica layer as a good lubricant, as shown in reactions and . , However, water in the Si 3 N 4 /metal interface could be insufficient under boundary lubrication, which is difficult to form a stable colloidal silica layer . Meanwhile, in PDA-aq, the PDA tribofilm is hydrophilic and can strongly form a stable “solid-like” water film on the interface .…”
Section: Resultsmentioning
confidence: 95%
“…The diameter of the wear scar is close to 200 μm, and the surface is quite rough. The results imply that the Si 3 N 4 ball is seriously worn and cannot exert self-lubricating properties because of insufficient water on the friction interfaces under boundary lubrication . In contrast, the wear scar on the steel disc in GO-aq becomes smaller and shallower (Figure d) because the adsorption of GO on the contact interface is beneficial for wear reduction.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The flash point temperature during polishing excites the oxidation reaction in Equations ( 18)- (20). Therefore, the temperature of the test environment is so low that it does not affect the occurrence of thetribochemical reaction and has little effect on friction behavior [48,49].…”
Section: Mechanism Of Tribochemical Oxidation Reaction On the Surface...mentioning
confidence: 99%
“…Tribometer dynamics can be identified in sensor data using appropriate filtering techniques and can be segregated effectively from signal noise. In particular, in cases where only long-time transient behavior is considered, e.g., when only one average value of the coefficient of friction (CoF) is reported per stroke or cycle [17,19,20], a meticulous analysis of time-resolved sensor data may increase the significance of the reported experimental results [21,22].…”
Section: Introductionmentioning
confidence: 99%